IMPLEMENTASI PERATURAN DAERAH KOTA BUKITTINGGI NOMOR 2 TAHUN 2015 TENTANG PENCEGAHAN DAN PENANGGULANGAN BAHAYA KEBAKARAN - Yelni Aprina; Rahmadani Yusran (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
ABSTRAK The purpose of this research was to determine the implementation of the Regional Regulation of Bukittinggi cities Number 2 of 2015 about Fire hazard Prevention and countermeasures. This research is a qualitative research and uses descriptive methods. The research informants were determined using purposive sampling techniques. including the head of the treatise section and the session of the Bukittinggi Cities DPRD, Head of sub-division Documentation and legal counseling of Bukittinggi cities, The head of the prevention section and the head of the operational section of the fire department, Head of K3L PLN of Bukittinggi cities, fire victim and society of Bukittinggi cities. Data collection techniques carried out by observation, interview and study documentation. To test the validity of the data using source triangulation techniques. The results showed that the implementation of local regulations have not been implemented optimally, there are still some aspects that still need attention such as aspects of the target group, aspects of the desired degree of change, resources involved, characteristics of the ruling institutions as well as compliance and responsiveness. There are supporting factors in the implementation of regional regulations such as the socialization carried out by related parties, the implementation of the Regional Regulation is also supported by the provision of training and education to officers so that they have the ability and skills in their fields. Resources and lack of commitment in implementing local regulations. So that efforts are needed by the government in implementing policies. keywords: Implementation of policies, prevention and mitigation of fire hazards, regional regulation of Bukittinggi cities